Physical Activity, Sleep Quality, And Gadget Use As Risk Factors For Anemia In Adolescent Girls: A Systematic Literature Review - Yuni Purwanti; Dewi Purnamawati (CV. AFDIFAL MAJU BERKAH, 2026)
Anemia among adolescent girls remains a significant public health problem because it can adversely affect growth, learning capacity, productivity, and future reproductive health. In addition to nutritional factors, modern lifestyle changes—including physical activity, sleep quality, and gadget use—are increasingly recognized as potential contributors to anemia risk. This study aimed to synthesize scientific evidence regarding the association of physical activity, sleep quality, and gadget use with anemia among adolescent girls. This study aimed to analyze and synthesize scientific evidence regarding the association of physical activity, sleep quality, and gadget use with anemia among adolescent girls and to identify the underlying mechanisms linking these factors to anemia. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature searches were conducted in the PubMed, Scopus, ScienceDirect, ProQuest, Google Scholar, and Garuda databases for articles published between 2020 and 2025. Studies were selected based on predefined inclusion and exclusion criteria, assessed for methodological quality, and analyzed using narrative synthesis and thematic analysis. A total of 25 articles met the eligibility criteria and were included in the final synthesis. The review findings indicated that unbalanced physical activity, poor sleep quality, and excessive gadget use were associated with an increased risk of anemia among adolescent girls. Both insufficient and excessive physical activity without adequate nutritional support may affect hemoglobin levels. Poor sleep quality was linked to impaired iron metabolism and hemoglobin synthesis, while excessive gadget use indirectly contributed to anemia through increased screen time, sedentary behavior, and reduced sleep quality. These findings suggest that these three lifestyle factors interact and collectively influence the risk of anemia. In conclusion, preventing anemia among adolescent girls requires a comprehensive approach that addresses not only nutritional factors but also healthy physical activity, adequate sleep, and responsible gadget use. The findings provide evidence for developing adolescent health programs and future research on lifestyle determinants of anemia.